TUTOR’S ABILITY IN IMPLEMENTATION PROBLEM-BASED LEARNING IN A MEDICAL FACULTY - Indah Puspasari Kiay Demak; Puspita Sari; Andi Alfia Muthmainnah Tanra (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: Problem-based learning is a student-centered learning approach. PBL activities include an implementation of tutorial discussions that will be facilitated by the tutor. The active role of students to search the learning resources and describe it in tutorial discussion until desired learning objectives and expected competencies reached can not be separated from the role of tutor. The aim of this study was to evaluate tutor’s ability in implementation problem-based learning in Medical Faculty Tadulako University.Methods: This was a cross sectional study with quantitative descriptive approach. The subjects were all students in second, third and fourth year. Data collected from 5 likert scale questionnaire of tutor’s ability.Results: The highest score of tutor’s ability was helping students’ comprehend principles theories in constructive learning, make conclusion in self directed learning, and got constructive feedback in collaborative learning. In contextual learning, for second and fourth year students was to apply knowledge in similar situation, while for third year was to apply knowledge in cases discused.Conclusion: Tutor’s ability was high for all PBL aspects, which contextual learning was the highest, while constructive leaning was the lowest.